2020
DOI: 10.1149/1945-7111/abc10e
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Corrosion Resistance of Additively Manufactured 316L Stainless Steel After Heat Treatment

Abstract: The microstructures and passivation behavior of selective laser melted 316L stainless steel (SLM SS316L) after various heat treatments (500 °C, 950 °C, and 1100 °C) were investigated. The electrochemical results showed that the SLM SS316L sample that was heat treated at 950 °C exhibited the lowest passive current density. The microstructural characterization analysis indicated that the subgrain structures transformed from dislocation-rich subgrain boundaries into island-like cellular trace structures after hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…Kong et al reported that a thermal treatment at 650 °C for 30 min did not modify the passive behavior of as-built L-PBF AISI 316L stainless steel, while recrystallization annealing at 1050 °C for 30 min promoted the formation of a thicker and more protective oxide film due to the homogenization effect of the thermal treatment at a high temperature [ 24 , 25 ]. Similar results were reported by Zhou et al, which showed that a thermal treatment at 950 °C for 4 h produced a homogenization effect on the microstructure and distribution of alloying elements [ 37 ]. In contrast, thermal treatment at 1100 °C reduced the corrosion resistance due to the formation of a high amount of Cr(OH) 2 and to the segregation of alloying elements after complete recrystallization [ 37 ].…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…Kong et al reported that a thermal treatment at 650 °C for 30 min did not modify the passive behavior of as-built L-PBF AISI 316L stainless steel, while recrystallization annealing at 1050 °C for 30 min promoted the formation of a thicker and more protective oxide film due to the homogenization effect of the thermal treatment at a high temperature [ 24 , 25 ]. Similar results were reported by Zhou et al, which showed that a thermal treatment at 950 °C for 4 h produced a homogenization effect on the microstructure and distribution of alloying elements [ 37 ]. In contrast, thermal treatment at 1100 °C reduced the corrosion resistance due to the formation of a high amount of Cr(OH) 2 and to the segregation of alloying elements after complete recrystallization [ 37 ].…”
Section: Introductionsupporting
confidence: 88%
“…Similar results were reported by Zhou et al, which showed that a thermal treatment at 950 °C for 4 h produced a homogenization effect on the microstructure and distribution of alloying elements [ 37 ]. In contrast, thermal treatment at 1100 °C reduced the corrosion resistance due to the formation of a high amount of Cr(OH) 2 and to the segregation of alloying elements after complete recrystallization [ 37 ]. Moreover, it was hypothesized that nanoscale inclusions of silicon oxide observed after heat treatment at 1100 °C could promote pit initiation [ 37 ].…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…The positive influence of the ratio O 2À / OH À in the native passive film (section 3.2) is then counterbalanced by the negative role of carbides. The corrosion resistance of 316L elaborated by SLM can increase after certain heat treatment, while others may reduce it ( Ref 17,18,28,29). It depends on modifications of the microstructure and physicalchemical properties of the passive film formed after aging in aqueous solutions.…”
Section: Corrosion Behavior Of Samples In 35wt% Naclmentioning
confidence: 99%